DIFUSI INOVASI DALAM MENINGKATKAN PARTISIPASI MASYARAKAT AKAN KELESTARIAN LINGKUNGAN - Ahmad, Rizal (SOSIETAS, 2016)
Lack of peopleâ€™s awareness in maintaining environment demands human being to keep it clean. Thorugh of creativity and innovative are poured into action by Kuya Tilu Belas, peopleâ€™s role as agent of change is trying to be risen again so that revitalization process to keep river staying clean will immediatelly occur as it was before. The result of this study exposes that conceptual mode has been spreaded by community to society of RW 13 Tamansari outcoming a thought of movement â€œCikapundung cleanâ€.To communicate this idea, community uses two approaches (intrapersonal and mass media) to ease society in looking for information about movement of Cikapundung clean, from this study shows that four RTs receive and adapt ideas while three of them choose no longer to adapt this diffusion and innovation.Â